EntrepRise Food Garden in Facebook: The Efficiency of Social Advertising among College Students - Aguilar, Teresa A.; Tombocon, Nonalyn D. (Future Science / FSH-PH Publications, 2023)
One of the most important social developments of the past ten years has been Facebook's meteoric ascent to prominence as a social networking site. Organizations seek to use Facebook for a variety of reasons, including to exchange and disseminate information, sell goods or services, maintain contact with current and new consumers, learn more about their customers, and obtain additional benefits. Some of these objectives are listed below. This study's objective is to investigate and evaluate the efficiency of using Facebook as a medium for advertising purposes. Facebook is the focus of this study. It will make an effort to explain how effective Facebook is as a site for advertising and how that relates to the benefits that may be acquired, and it will do so by demonstrating how effective Facebook is as a site for advertising. College students who frequently encounter Facebook adverts on their mobile devices are going to be the focus of a survey that will be carried out with the use of a random sampling method. Facebook is helpful in describing new products and promoting them in a way that either creates or improves brand impressions in a range of markets and cultural contexts. This may be accomplished in different ways. It is essential for businesses to have a working knowledge of how to promote on Facebook and other social media platforms, particularly if they intend to expand their customer base among college students. In particular, it is essential for businesses to have a working knowledge of how to promote on Instagram.